Case Report: Methotrexate and hydroxychloroquine in combination for the treatment of NOD2-mutation-associated Blau syndrome - Jensen, Mary Ellen; Harrell, Katelin; McBride, Jeffrey D. (Frontiers in Immunology, 2023)
Mutations in Nucleotide Binding Oligomerization Domain Containing 2 receptor (NOD2) are associated with Blau Syndrome (also known as early-onset sarcoidosis) – a rare autosomal dominant, chronic granulomatous disease that typically presents before five years of age. Blau syndrome is characterized by the clinical triad of arthritis, granulomatous dermatitis, and recurrent uveitis. Here, we report a case of NOD2-mutation-associated early-onset sarcoidosis in which a combination of methotrexate and hydroxychloroquine was used to achieve improvement in arthritis, granulomatous dermatitis, and uveitis. A 13-month-old male presented with a sudden-onset cutaneous eruption affecting the face, trunk, and extremities that initially mimicked popular atopic dermatitis but progressively worsened despite topical steroid therapy. The patient had no other known medical comorbidities or abnormalities except for heterochromia of the right eye. However, prior to presentation to dermatology, the patient began experiencing frequent falls, conjunctival injection, and apparent eye and joint pain. Skin biopsy from the right shoulder demonstrated rounded aggregates of epithelioid histocytes and multinucleated giant cells without a significant lymphocytic component (“naked granulomas”), consistent with sarcoidal granulomatous dermatitis. Given the concern for Blau syndrome, patient was sent for evaluation by ophthalmology and was found to have bilateral subconjunctival nodules. Our patient underwent genetic testing and was found to have a mutation in codon 1000 C > T (protein R334W) in the NOD2 gene. The patient responded to oral prednisilone 2mg/kg/day for 8 weeks, but quickly relapsed, requiring a second 8-week course with taper upon starting methotrexate 7.5 mg subcutaneously weekly with 1mg folic acid orally daily. After 8 weeks on methotrexate, due to persistent arthritis, conjunctival injection and pruritus, and in consultation with rheumatology, the patient was started on hydroxychloroquine 75 mg orally daily along with continuation of 7.5 mg methotrexate subcutaneously weekly for 8 weeks, achieving significant reduction in arthritis, pruritus, and uveitis. After 8 weeks of this combination therapy, due to concerns of long-term macular toxicity, hydroxychloroquine was discontinued in favor of continuing methotrexate alone. Patient has remained free of significant side effects and stable with good disease control on 7.5 mg methotrexate weekly injected subcutaneously.